2008
DOI: 10.1152/jn.90526.2008
|View full text |Cite
|
Sign up to set email alerts
|

Complex Spike Activity in the Oculomotor Vermis of the Cerebellum: A Vectorial Error Signal for Saccade Motor Learning?

Abstract: Soetedjo R, Kojima Y, Fuchs AF. Complex spike activity in the oculomotor vermis of the cerebellum: a vectorial error signal for saccade motor learning ? J Neurophysiol 100: 1949-1966, 2008. First published July 23, 2008 doi:10.1152/jn.90526.2008. Brain stem signals that generate saccadic eye movements originate in the superior colliculus. They reach the pontine burst generator for horizontal saccades via short-latency pathways and a longer pathway through the oculomotor vermis (OMV) of the cerebellum. Lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
121
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 41 publications
11
121
1
Order By: Relevance
“…However, these findings do not necessarily indicate that the learning signal is purely visual. For example, as speculated in a recent study (Soetedjo et al, 2008), the "quasi-visual" cells in the deeper layers of the SC (Mays and Sparks, 1980;Sparks and Hartwich-Young, 1989), which exhibit apparent visual response Figure 10. a, Relationship between the direction of the endpoint shift (ordinate) and that of the optimal vector for SC stimulation site (abscissa) for 32 experiments, shown separately for left SC and right SC stimulation.…”
Section: Nature Of a Learning Signal And Its Transmission Pathway To mentioning
confidence: 68%
See 1 more Smart Citation
“…However, these findings do not necessarily indicate that the learning signal is purely visual. For example, as speculated in a recent study (Soetedjo et al, 2008), the "quasi-visual" cells in the deeper layers of the SC (Mays and Sparks, 1980;Sparks and Hartwich-Young, 1989), which exhibit apparent visual response Figure 10. a, Relationship between the direction of the endpoint shift (ordinate) and that of the optimal vector for SC stimulation site (abscissa) for 32 experiments, shown separately for left SC and right SC stimulation.…”
Section: Nature Of a Learning Signal And Its Transmission Pathway To mentioning
confidence: 68%
“…This tecto-olivo-cerebellar pathway has been postulated to transmit a learning signal in modeling studies (Dean et al, 1994;Fujita, 2005) but its function remains to be defined. Recent recording studies have provided strong support for the olivary relay of learning signals (Soetedjo and Fuchs, 2006;Soetedjo et al, 2008). Climbing fiber responses of Purkinje cells in the oculomotor vermis carry error information during saccade adaptation.…”
Section: Nature Of a Learning Signal And Its Transmission Pathway To mentioning
confidence: 99%
“…5. Reanalysis of data from Soetedjo et al (2008). This plot is a summary of n ϭ 18 Purkinje cells in the cerebellum showing the probability of a complex spike in response to errors of various sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Complex spikes (CSs) that are generated by climbing fiber inputs onto Purkinje cells of the cerebellum are considered to be the biological representation of an error signal (Kitazawa et al 1998). However, when the probability of a CS was measured in response to various error sizes, the probability was high for small errors but decreased for larger errors (Soetedjo et al 2008). This result is inconsistent with the idea that CSs encode an error, and instead indicates that error size may play a role in plasticity of Purkinje cells.…”
mentioning
confidence: 99%
“…A similar if rarer behavior can be seen in the superior colliculus (Walker et al, 1995). In the cerebellum, Soetedjo et al (2008) showed that complex spikes in the vermis encode the direction of the visual error between 100 and 150 ms after saccade end.…”
Section: Temporal Dynamics Of the Sensorimotor Integrationmentioning
confidence: 71%